Estudo das reações no sistema 'CU'-'AL'-'AG'-'MN' - Magdalena, Aroldo Geraldo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, the reactions that occur in the quaternary system Cu-Al-Ag-Mn, in the Cu-rich region and at the beginning of the eutectoid transition occurrence was studied in Cu- 9wt.%Al alloys with additions of 3, 4 and 5 wt.%Ag and 4, 6 and 8 wt.%Mn using optical (OM) and scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Xray diffraction (XRD), energy dispersion X-ray analysis (EDX), electrical resistivity changes measurements with temperature and microhardness changes measurements with temperature and time. Results obtained for stable transitions showed that the reactions sequence is (α2→α), β1→ β-(T7-Cu2MnAl) e T3-(Cu3Mn2Al) → β-(T7-Cu2MnAl). Additions of Mn increase the β phase region and Ag additions promote the precipitation of an Ag-rich phase from the Cu-rich matrix. The presence of Mn seems to change the precipitates adherence to the matrix. For metastable transitions the observed reactions was: α phase precipitation from the martensitic phase, β’→β1(DO3) transition and partial decomposition of the β1 phase on the α, γ and T3 phases, β1(DO3)→β2(B2) and β2(B2)→β(A2) transitions. For alloys with Ag additions other two reactions were observed, Ag-rich phase precipitation and dissolution. Results obtained from isothermal ageing of the alloys and β phase formation non-isothermal kinetics showed that there is a solubility maximum for Ag and that it is about 6wt.%Mn. Results obtained for aged alloys in the considered time and temperature range showed the stabilization of the martensitic phase and the consumption of the α phase as the dominant reaction for the Cu- 9%Al-4%Mn alloy. For the rest of studied alloys the dominant reaction is α phase precipitation with growing of bainitic plates due to interface diffusion along grain boundaries between the martensitic and the bainitic phase. In the Cu-9%Al-4%Mn alloy Ag dissolution into the matrix increases the Mn relative fraction and...

Neste projeto, estudaram-se as reações que ocorrem no sistema quaternário Cu-Al-Ag- Mn, na região rica em cobre e no início do intervalo de existência da transformação eutetóide, em ligas de Cu-9%Al com adições de 3, 4 e 5%Ag e 4, 6 e 8%Mn (m/m), utilizando-se metalografia por microscopia óptica (MO) e eletrônica de varredura (MEV), calorimetria exploratória diferencial (DSC), difração de raios X (DRX), análise por dispersão de energias de raios X (EDX), medidas de variação da resistividade elétrica com a temperatura e medidas de variação da microdureza com a temperatura e o tempo. Os resultados obtidos para as transições estáveis mostraram a seguinte sequencia de reações: (α2→α), β1→ β-(T7-Cu2MnAl) e T3-(Cu3Mn2Al) → β-(T7-Cu2MnAl). As adições de Mn ampliam a região de existência da fase β e os resultados ainda indicaram que a precipitação da fase rica em Ag ocorre a partir da matriz rica em cobre e a presença de Mn deve alterar a aderência destes precipitados na matriz. Os resultados obtidos para as transições metaestáveis mostraram as seguintes reações: precipitação da fase α a partir da fase martensítica, transição β’→β1(DO3) e parte da decomposição da fase β1 nas fases α, γ e T3, transição β1(DO3)→β2(B2) e a transição β2(B2)→β(A2). Para as ligas contendo Ag, além das reações já citadas pode-se observar a ocorrência de mais duas reações: precipitação e dissolução de Ag. Os resultados obtidos durante o envelhecimento isotérmico das ligas e para a cinética não isotérmica de formação da fase β mostraram que existe um máximo de solubilidade da Ag no Mn, que deve ficar em torno de 6% Mn. Os resultados obtidos para as ligas envelhecidas no intervalo de tempo e temperatura considerados mostraram que a fase martensítica foi estabilizada e a reação dominante para a liga Cu-9%Al-4%Mn é a reação de consumo da fase α e para as demais ligas a reação...
Keywords: Físico-química; Transição de fase; Ligas metálicas; Comportamento térmico; Microdureza; Thermal behavior